2001
DOI: 10.1016/s0025-5408(01)00622-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium aluminate (MgAl2O4) spinel produced via self-heat-sustained (SHS) technique

Abstract: Usage of a new but simple and reactive technique employing metallic aluminum as one of the reactants to produce very high phase-purity magnesium aluminate powder under rather mild experimental conditions is described. Low temperature melting of aluminum and subsequent exothermic reaction between molten aluminum and magnesia appeared to have led to the powder with a very high fraction of the spinel phase with small particle size and narrow particle size distribution. This powder upon sintering for 4h at 1600°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Therefore, the observed phase evolution cannot be explained by solid-state reaction/sintering. Nevertheless, the formation of two spinel compositions is straightforward in the presence of local liquid-film at the particle contacts, the temperature of which is above the congruent temperature of spinel, 2135 °C [25] (Figure 2). As mentioned above, immediately after the local melting, the local contact temperature defines the local composition according to the liquidus line.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed phase evolution cannot be explained by solid-state reaction/sintering. Nevertheless, the formation of two spinel compositions is straightforward in the presence of local liquid-film at the particle contacts, the temperature of which is above the congruent temperature of spinel, 2135 °C [25] (Figure 2). As mentioned above, immediately after the local melting, the local contact temperature defines the local composition according to the liquidus line.…”
Section: Discussionmentioning
confidence: 99%
“…[16] 2.340e0.451 Â 10 À3 T 3.000e0.577 Â 10 À3 T g ss -specific grain boundary energy, g sg -specific surgace energy, T-temperature in K. different microstructures of green bodies. It was found that the critical density (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas alumina and magnesia-alumina spinel are single phase materials with well-defined theoretical density (3.99 g/cm 3 for alumina [14,15], resp. 3.58 g/cm 3 for MgAl 2 O 4 [16,17]), theoretical densities as well as lattice structure of yttria stabilized zirconias varies according to content of yttria and temperature. From equilibrium phase diagram it follows that for sintering temperatures above 1100 C ZrO 2 doped by 8 mol% Y 2 O 3 is cubic and ZrO 2 doped by 3 mol% Y 2 O 3 is a mixture of tetragonal and cubic phases with fractions depending on annealing temperature [18].…”
Section: Methodsmentioning
confidence: 98%
“…Accordingly, it is imperative to investigate their formation mechanism and ability to nucleate aluminum grains in order to facilitate the use of oxides for the grain refinement and structural uniformity of the alloys. MgAl 2 O 4 with the density of 3.65 g/cm 3 exhibits a congruent melting point at 2315 °C in the MgO‐Al 2 O 3 phase diagram and shows low coefficient of thermal expansion, good thermal shock resistance, and high electrical resistivity . The lattice parameter for the close‐packed oxygen anion sublattice of the MgAl 2 O 4 unit cell is nearly equal to that of aluminum unit cell with the same face‐centered cubic structure.…”
Section: Introductionmentioning
confidence: 98%